Perceptions of Marine Environmental Issues by Saudi Citizens - Almahasheer, Hanan; Duarte, Carlos M. (Frontiers in Marine Science, 2020)
We depend on the sea, economically, social well-being and for the quality of our lives. Yet, direct and indirect human activities have affected the marine environment causing many problems, such as overfishing and pollution at the local scale and ocean warming and acidification at the global one. Hence, addressing the cumulative effects of these activities is required to conserve the marine environment for our current and future generations. Social commitment and support for these actions depends, however, on awareness, and requires, therefore, understand citizen’s awareness and perceptions on these issues. We assessed the awareness and perceptions of Saudi citizens on ocean issues through an online questionnaire about environmental issues globally and in the country. The survey was completed by 1,524 Saudi citizens eighteen-year-old and above, with different geographic distributions, gender and educational status. Participants identified climate change within the top three global problems, with variable level of information and trust on different sources of environmental information. Pollution, specifically littering, sewage pollution and oil pollution were identified as the top three major marine issues in Saudi Arabia, with respondents demanding immediate action through imposing fines to polluters and more regulatory constraints to activities that act as sources of pollution, as well as supporting research in science and technologies to address these environmental issues.